Organism Profile in Periprosthetic Joint Infection: Pathogens Differ at Two Arthroplasty Infection Referral Centers in Europe and in the United States - Aggarwal, Vinay K.; Bakhshi, Hooman; Ecker, Niklas Unter; Parvizi, Javad; Gehrke, Thorsten; Kendoff, Daniel (The Journal of Knee Surgery, 2014)
Infecting microorganism is a strong predictor of treatment success for periprosthetic joint infection (PJI). The purpose of this study was to compare the infecting pathogens causing PJI at two large infection referral centers in the United States and in Europe. In this study, 898 consecutive cases of PJI were identified at the HELIOS ENDO-Klinik Hamburg in Europe and 772 cases were identified at the Rothman Institute in the United States. The incidence of organisms at the HELIOS ENDO-Klinik Hamburg versus the Rothman Institute was: coagulase-negative Staphylococcus (39.3 vs. 20.2%), S. aureus (13.0 vs. 31.0%), Streptococcus (6.5 vs. 5.8%), Enterococcus (7.0 vs. 3.9%), anaerobic (9.0 vs. 0.9%), fungal (0.3 vs. 2.3%), mycobacterial (0 vs. 0.6%), polymicrobial (3.4 vs. 7.4%), culture negative (16.1 vs. 15.8%), and other organisms (0.9 vs. 5.4%). The percentage of methicillin-resistant S. aureus was significantly higher at the American center than at the European center (48.1 vs. 12.8%; p < 0.0001). Our findings show higher virulence and resistance organisms are more prevalent at a referral center in the United States compared with one in Europe.
Keywords: periprosthetic joint infection; PJI; arthroplasty; Europe; United States